THE EFFECT OF A SPEAKING FOR ACADEMIC PURPOSES LEARNING MODEL ON STUDENTS' ENGLISH PROPOSAL SEMINAR PRESENTATION ABILITY: A QUASI-EXPERIMENTAL STUDY - Nasriandi; Masruddin Asmid; Hikmawati (University of Kuningan, 2026)
The ability to present academic work in English is a critical yet underdeveloped competency among English Education (EED) students in Indonesian higher education. This quasi-experimental study investigated the effect of a Speaking for Academic Purposes (SAP) learning model on EED students' English proposal seminar presentation ability at Muhammadiyah University of Palopo. A non-equivalent control group design was employed, involving 60 sixth-semester students divided into an experimental group (n = 30) that received SAP model instruction over six sessions, and a control group (n = 30) that received conventional speaking instruction. Both groups completed pre-tests and post-tests assessed using an analytical speaking rubric covering five dimensions: content, language accuracy, fluency, discourse organization, and delivery. Data were analyzed using an independent-samples t-test to compare post-test means between groups, and a paired-samples t-test to measure within-group gains. Results showed that the experimental group achieved a significantly higher post-test mean (M = 82.8, SD = 7.2) compared to the control group (M = 67.4, SD = 9.1), with a statistically significant between-group difference (t(58) = 7.34, p < .001, d = 1.89). Within the experimental group, all five rubric dimensions showed significant improvement, with the largest gains in Discourse Organization (+47.8%) and Fluency (+45.0%). These findings provide empirical evidence that the SAP model, integrating genre-based instruction, structured rehearsal, peer feedback, and reflective practice, is significantly more effective than conventional instruction in improving students' academic speaking performance. Implications for English Education curriculum design and pedagogical practice are discussed.